Female genital cutting and the slave trade - Lucia Corno; Eliana La Ferrara; Alessandra Voena (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2025)
This paper investigates the historical origins of female genital cutting (FGC). We test the historical hypothesis that FGC is associated with the Red Sea route of the African slave trade, where women were typically sold as concubines in the Middle East and infibulation was used as a means to preserve virginity. Using individual-level data from 28 African countries combined with historical records of Red Sea slave shipments from 1400 to 1900, we find that women from ethnic groups whose ancestors experienced greater exposure to the Red Sea slave trade are more likely to undergo infibulation or circumcision today. They are also more inclined to support the continuation of this practice. Our findings are robust to instrumenting Red Sea slave exports with the distance to the nearest port used for this route. We also leverage a dataset on oral traditions (Folklore) to show that greater exposure to the Red Sea slave trade correlates with a stronger association between infibulation and the cultural values of chastity and purity, which may have facilitated the diffusion of infibulation among local populations
Keywords: O10; I11; 330; FGC; FGM; social norms; slave trade; Africa